Inhibition of MORC2 Mediates HDAC4 to Promote Cellular Senescence through p53/p21 Signaling Axis - Kepeng Ou; Youjian Li; Yiling Long; Yafei Luo; Dianyong Tang; Zhongzhu Chen (Molecules, 2022)
(1) Background: Colorectal cancer (CRC) is a common gastrointestinal malignancy, accounting for the second largest gastrointestinal tumor. MORC2, a newly discovered chromatin remodeling protein, plays an important role in the biological processes of various cancers. However, the potential mechanistic role of MORC2 in promoting proliferation of CRC carcinoma remains unclear. (2) Methods: The Cancer Genome Atlas database was analyzed using bioinformatics to obtain gene expression and clinical prognosis data. The cell proliferation was assessed by CCK8 and EdU assays, as well as xenograft. SA-beta-gal staining, Western blot, and ELISA assay were using to assess the cell senescence and potential mechanism. (3) Results: Our data showed that MORC2 expression was elevated in CRC patients. Depletion of MORC2 inhibited cellular proliferation both in vivo and in vitro. Further studies showed that the depletion of MORC2 enhanced p21 and p53 expression through decreasing HDAC4 and increasing pro-inflammatory factors IL-6 and IL-8, thus, promoting cellular senescence. (4) Conclusions: We concluded that increased MORC2 expression in CRC might play a critical role in tumorigenesis by regulating the cellular senescence, in addition, MORC2 could be a novel biomarker for clinical outcomes and prognosis and a treatment target for CRC.